EFFECT OF CHROMIUM ON FATTY ACIDS COMPOSITION OF SCALY CARP (CYPRINUS CARPIO CARPIO LINNAEUS, 1758) - Coban, Ozlem Emir; Yilmaz, Okkes (Parlar Scientific Publications (P S P), 2011)
In this study, the effects of different concentrations (7.5, 15, 30 and 60 ppb) of chromium on the fatty acid composition of Cyprinus carpio carpio that consumed favorably by the public were investigated. It was determined from the results of 21 days Cr(+3) exposure period of fish, depending on Cr(+3) concentration the amounts of crude fat, saturated fatty acid and unsaturated fatty acids in fish were decreased when compared with control group (p< 0.05). The most effect was determined in 60 ppb Cr(+3) concentration (p<0.01).
Keywords: Cyprinus carpio carpio; Fatty acids; Crude fat %; Cr(+3)